Mineral composition and pore structure on spontaneous imbibition in tight sandstone reservoirs - Chen Yang; Erlong Yang (Scientific Reports, 2025)
Abstract The pore structure of tight oil reservoirs is extremely complex, with a wide range of pore sizes, diverse pore types, and well-developed nanopores and throats. Although researchers have conducted in-depth studies on the mechanism of spontaneous imbibition, issues such as low recovery and short imbibition distance have not been well explained. This study characterized the relationship between mineral composition and pore types through XRD and SEM, and combined NMR-C, LF-NMR, and micro-CT to characterize the pore size distribution of tight sandstones. The effects of pore structure characteristics and displaced phase properties on spontaneous imbibition were investigated. Using NMR-C and low-temperature evaporation methods, the proportions of free water and bound water in pores with diameters ranging from 3.33 to 600 nm were quantitatively characterized. The results indicated that the maximum pore size and its proportion were the primary factors influencing permeability, whereas the content of small pores and mesopores played a crucial role in accessing the quality of connectivity. The content of micron-scale pores in the core exhibited a positive correlation with quartz content, whereas the amounts of feldspar and clay minerals were closely associated with the development of nanoscale pores. The proportion of large pores and the viscosity of the displaced phase had the most significant effect on imbibition efficiency, followed by the homogeneity of pore distribution and connectivity. Moreover, the bound water content in nanopores exceeded 50% of the pore volume, which reduced pore size and connectivity during the imbibition process, resulting in a shorter imbibition distance. This study investigated the effect of pore structure and mineral composition on spontaneous imbibition and examined the factors contributing to the limited imbibition distance in tight oil reservoir development. The findings offer new insights and strategies for enhancing recovery in tight oil reservoirs.